The Peristaltic Flow of Jeffrey Fluid through a Flexible Channel - Al-Khafajy, Dheia G. Salih; AL-Khalidi, Noor AL-Huda Kareem (Iraqi Journal of Science, 2022)
The purpose of this study is to calculate the effect of the elastic wall of a hollow channel of Jeffrey’s fluid by peristaltic flow through two concentric cylinders. The inside tube is cylindrical and the outside is a regular elastic wall in the shape of a sine wave. Using the cylindrical coordinates and assuming a very short wavelength relative to the width of the channel to its length and using governing equations for Jeffrey’s fluid in Navier-Stokes equations, the results of the problem are obtained. Through the Mathematica program these results are analysed.